PERENCANAAN BANGUNAN RUMAH SAKIT 10 LANTAI DENGAN SISTEM SRPMK - brian alfandi (Structure, 2025)
Â Abstract This journal focuses on planning the structure of a 10-story hospital building by considering the geographical challenges of Indonesia, especially Tangerang district which is prone to earthquakes. In an effort to produce structures that are strong against earthquake loads and efficient, this journal adopts a structural system method, namely the Special Moment Resisting Frame System (SRPMK) based on SNI 2847-2019, SNI 1726-2019 and SNI 1727-2020 and other regulations applicable in Indonesia for support the planning of earthquake resistant buildings. This journal involves several stages, starting from the initial design stage, followed by structural modeling and analysis using ETABS software. Through this process, structural dimensions and calculations can be generated and evaluated. It is hoped that the results of this journal will provide useful guidance for students and planners in designing high-rise hospital buildings in earthquake-prone areas in general in Indonesia. By using the Special Moment Resisting Frame System (SRPMK), and complying with applicable regulations, it is hoped that the building structure can be designed to be resistant and function well in earthquake situations and be efficient.Keywords: Hospital Building Planning, SRPMK, ETABS